Survival Rate and Prognostic Factors on Survival of Patients with Oral Squamous Cell Carcinoma - Sererat, Chairat; Sererat, Wipada (Journal of The Department of Medical Services, 2025)
Background: Oral cavity squamous cell carcinoma (OCSCC) is a cancer that arises from the epithelial cells in the oral cavity. It is common in adults and has a high incidence in many countries, including Thailand. Objective: To study the survival rate and prognostic factors for survival in patients with OCSCC treated at Roi Et Hospital. Methods: A retrospective cohort study was conducted by collecting data from patient medical records between January 1, 2015, and December 31, 2021, with follow-up until December 31, 2023. Data were analyzed using descriptive statistics, Kaplan-Meier survival method, and Cox proportional hazard model (p < .05). Results: A total of 273 patients were included. The majority were female (69.37%) with a mean age of 66.14 years (±12.78). A total follow-up of 1,116 person-months was completed. There were 222 deaths, with an incidence rate of 19.87 per 100 person-months (95%CI: 12.23, 23.75). The median survival time was 1.66 years. The survival rates at 1, 3, 5, and 10 years were 62.89%, 42.66%, 32.73%, and 19.93%, respectively. Risk factors for death included poorly differentiated histology (adjHR = 2.91; 95%CI: 1.61, 7.22), and cancer stages 2 (adjHR = 1.90; 95%CI: 1.19, 3.00), 3 (adjHR = 2.65; 95%CI: 1.62, 4.32), and 4 (adjHR = 3.71; 95%CI: 2.13, 6.47). Conclusion: Patients with oral cancer at Roi Et Hospital had a median survival time of 1.66 years, with a 5-year survival rate of 32.73%. Poor histology grading and advanced disease stage were significant prognostic factors that reduced the survival rate.